SPONTANEOUS MISCARRIAGE: STATE STUDY QUESTIONS - E. I. Borovkova; I. V. Martynova (Исследования и практика в медицине)
Review of the literature devoted to the problem of early pregnancy losses. Presented modern classification, The etiology and pathogenesis of complications, diagnostic criteria and differential diagnosis, and treatment standards and opportunities for prevention.